Advances in External Beam Radiation Therapy and Brachytherapy for Cervical Cancer. Issue 9 (September 2021) - Williamson, C.W.; Liu, H.C.; Mayadev, J.; Mell, L.K.
Abstract: The standard of care for the definitive treatment of locoregionally advanced cervical cancer is external beam radiation therapy (EBRT) with concurrent chemotherapy followed by a brachytherapy boost. Historically, EBRT was delivered via a two-dimensional technique based primarily on bony landmarks. This gave way to three-dimensional conformal radiation therapy, which allows for dose calculation and adjustment based on individual tumour and patient anatomy. Further technological advances have established intensity-modulated radiation therapy (IMRT) as a standard treatment modality, given the ability to maintain tumoricidal doses to target volumes while reducing unwanted radiation dose to nearby critical structures, thereby reducing toxicity. Routine image guidance allows for increased confidence in patient alignment prior to treatment, and the ability to visualise the daily position of the targets and organs at risk has been instrumental in allowing safe reductions in treated volumes. Additional EBRT technologies, including proton therapy and stereotactic body radiation therapy, may further improve the therapeutic index. In the realm of brachytherapy, a shift from point-based dose planning to image-guided brachytherapy has been associated with improved local control and reduced toxicity, with additional refinement ongoing. Here we will discuss these advances, the supporting data and future directions.